2015
DOI: 10.1037/dev0000054
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of marijuana use from adolescence into adulthood: Environmental and individual correlates.

Abstract: This study sought to identify trajectories of marijuana use in the Seattle Social Development Project (n = 808) sample from age 14 through 30, and to examine the extent to which individuals in these trajectories differed in their substance use problems, mental health, problem behavior, economic outcomes, and positive functioning at age 33. In addition, analyses examined between-trajectory differences in family, peer, school, neighborhood, individual, mental health, and substance use factors at key developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 56 publications
5
87
0
Order By: Relevance
“…Based on research cited in the conceptual model above, we hypothesize that all of these risk and protective factors will differentiate adolescent monthly marijuana users from nonusers. Conversely, we hypothesize that only lower impulsivity in adolescence will be related to maturing out of marijuana use (Epstein et al, 2015; Labouvie & White, 2002). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on research cited in the conceptual model above, we hypothesize that all of these risk and protective factors will differentiate adolescent monthly marijuana users from nonusers. Conversely, we hypothesize that only lower impulsivity in adolescence will be related to maturing out of marijuana use (Epstein et al, 2015; Labouvie & White, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…In a study that overcame several of the limitations of previous research, Epstein et al (2015) examined trajectories of marijuana use from ages 14 to 30. They compared a group that used marijuana in adolescence but reduced their use after age 18 and stopped using by age 30 to a group that used similarly in adolescence but escalated their use in young adulthood and continued through age 30; predictors were measured at ages 10–14.…”
Section: Introductionmentioning
confidence: 99%
“…Many users initiate in adolescence, and some progress from occasional to persistent regular use (Substance Abuse and Mental Health Services Administration, 2013), but the associations between different developmental patterns of regular marijuana use over time and mental health outcomes are not well understood (Bechtold et al, 2015). A recent examination of trajectories of marijuana use from adolescence into adulthood using the present sample examined bivariate relationships between four identified patterns of marijuana users (chronic, adolescence-limited, late-onset, and nonusers) and a host of correlates at different developmental periods (Epstein et al, 2015). That study found mean differences in mental health outcomes at age 33; in general, chronic marijuana users had more symptoms of cannabis, alcohol, and tobacco use disorders than other types of users, and more symptoms of anxiety disorder than nonusers of marijuana.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies that have examined mental health outcomes of long-term marijuana use have focused on empirically derived, probabilistic patterns of use over time (e.g., Bechtold et al, 2015; Epstein et al, 2015), they have not focused specifically on regular use defined by specific a priori criteria. Furthermore, studies of the effects of persistent regular marijuana use (defined as a 5-level variable distinguishing between no use, no regular use, and regular use in 1 through 3 or more assessment points), have been limited to neuropsychological decline (e.g., Meier et al, 2012) and economic and social problems (Cerdá et al, 2016) later in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand motivations for MJ use, as heavy use in adolescence/young adulthood has been robustly linked with harms such as future substance dependence (Berge et al, 2015; Green et al, 2015), worse psychosocial functioning (Lagerberg et al, 2015; Wilkinson, Stefanovics, & Rosenheck, 2015) and worse academic outcomes (Epstein et al, 2015; Meier, Hill, Small, & Luthar, 2015; Silins et al, 2015). Young adults may both initiate and continue to use MJ in part due to social factors.…”
mentioning
confidence: 99%